Intersectoral collaboration - cooperation or competition? = Współpraca międzysektorowa - kooperacja czy konkurencja? - Łoś-Tomiak, Anna (Zielona Góra: Faculty of Economics and Management Press)
The paper presented the separation of the economy into three sectors. The mutual relations between sectors were described, with a particular reference to the cooperation of non-governmental organizations and public institutions. The role of non-profit institutions in the proper and efficient implementation of the social function of the state was highlighted.
Keywords: organizacje pozarządowe; sektor publiczny; instytucje non-profit; współpraca; non-governmental organizations; public sector; non-profit institutions; collaborations; cooperation